Pneumococcal conjugate vaccines PREVenar13 and SynflorIX in sequence or alone in high-risk Indigenous infants (PREV-IX_COMBO): protocol of a randomised controlled trial. Issue 1 (16th January 2015) - Leach, Amanda Jane; Mulholland, Edward Kim; Santosham, Mathu; Torzillo, Paul John; Brown, Ngiare Joy; McIntyre, Peter; Smith-Vaughan, Heidi; Skull, Sue; Balloch, Anne; Andrews, Ross; Carapetis, Jonathan; McDonnell, Joseph; et al.
Abstract : Introduction: Otitis media (OM) starts within weeks of birth in almost all Indigenous infants living in remote areas of the Northern Territory (NT). OM and associated hearing loss persist from infancy throughout childhood and often into adulthood. Educational and social opportunities are greatly compromised. Pneumococcus and non-typeable Haemophilus influenzae (NTHi) are major OM pathogens that densely colonise the nasopharynx and infect the middle ear from very early in life. Our hypothesis is that compared to current single vaccine schedules, a combination of vaccines starting at 1 month of age, may provide earlier, broadened protection. Methods and analyses: This randomised outcome assessor, blinded controlled trial will recruit 425 infants between 28 and 38 days of age and randomly allocate them (1:1:1) to one of three pneumococcal conjugate vaccine (PCV) schedules: Synflorix at 2, 4, 6 months of age, Prevenar13 at 2, 4 and 6 months of age, or an investigational schedule of Synflorix at 1, 2 and 4 months plus Prevenar13 at 6 months of age. The blinded primary outcomes at 7 months of age are immunogenicity of specific vaccine antigens (geometric mean concentration (GMC) and proportion of participants with above threshold GMC of 0.35 µg/L). Secondary outcomes at all timepoints are additional immunogenicity measures and proportion of participants with nasopharyngeal carriage of vaccine-type pneumococci and NTHi, and any OM, including any tympanic membrane perforation. Parental interviews will provide data on common risk factors for OM. Ethics and dissemination: Ethical approval has been obtained from NT Department of Health and Menzies HREC (EC00153), Central Australian HREC (EC00155) and West Australian Aboriginal Health Ethics Committee (WAAHEC- 377-12/2011). Final trial results, data analyses, interpretation and conclusions will be presented in appropriate written and oral formats to parents and guardians, participating communities, local, national and international conferences, and published in peer-reviewed open access journals. Trial registration numbers: ACTRN12610000544077 and NCT01174849 .